Online Learning Engagement in an EFL Writing Coursework: An Undergraduate Student’s Voice - Qatrunnida, Muthiah; Ardini, Anandayu Suri (Journal of English and Education (JEE), 2023)
This research aims to analyze the engagement of an EFL learner during an online writing course. The participant was a semester 3 student of English Education Department who had some experience and a great interest in writing skills in one of the universities in Indonesia. The data were collected through semi-structured interview and then were analyzed using thematic analysis. The finding shows that the participant has the three key aspects of learning engagement, there is behavioral, emotional, and cognitive engagement in the writing online courses. Though the participant had obstacles when involved in collaborative learning, she still managed to engage well in the online writing course in general. Thus, this study concluded that EFL learners who perform well in online collaborative writing tasks are more likely to have great engagement in online learning courses.